Pengaruh Green Intellectual Capital (Gic) Dan Islamic Corporate Governance (Icg) Terhadap Kinerja Perbankan Syariah Di Indonesia - Julia Handayani; Sriwardany Sriwardany; Ratna Sari Dewi; Alistraja Dison Silalahi (STIE Amkop Makassar, 2025)
This research aims to examine the influence of green intellectual capital and Islamic corporate governance on the performance of sharia banking in Indonesian. Sharia banking companies listed on the Indonesian Stock Exchange (IDX Syariah) in 2022-2024, measure green intellectual capital which is proxied by the green intellectual disclosure, Islamic corporate governance is proxied by measuring independent board of commissioners, managerial ownership, constitutional ownership, and audit committee. This research is quantitative research. Determining the sample using the purposive sampling method, the sample was obtained from 14 sharia banking companies in the 2022-2024 period so that 42 observation data were obtained. The data used is secondary data and the data analysis technique used is multiple linear regression method by conducting a series of classical assumption tests to ensure the suitability of the data. The data processing used in this research used multiple linear regression with the help of SPSS version 26 software. The results of this research show that green intellectual capital has a positive and significant effect on sharia banking performance, Islamic corporate governance has a positive and significant effect on sharia banking performance. Based on the results of the simultaneous test (F test), it shows that all independen variables have a effect simultaneously or together on the dependen variable.